Discrete element modelling and cavity expansion analysis of cone penetration testing - Falagush, Omar; McDowell, Glenn R.; Yu, Hai-Sui; de Bono, John P. (Springer Verlag, 2015)
This paper uses the discrete element method (DEM) in three dimensions to simulate cone penetration testing (CPT) of granular materials in a calibration chamber. Several researchers have used different numerical techniques such as strain path methods and finite element methods to study CPT problems. The DEM is a useful alternative tool for studying cone penetration problems because of its ability to provide micro mechanical insight into the behaviour of granular materials and cone penetration resistance. A 30° chamber segment and a particle refinement method were used for the simulations. Giving constant mass to each particle in the sample was found to reduce computational time significantly, without significantly affecting tip resistance. The effects of initial sample conditions and particle friction coefficient on tip resistance are investigated and found to have an important effect on the tip resistance. Biaxial test simulations using DEM are conducted to obtain the basic granular material properties for obtaining CPT analytical solutions based on continuum mechanics. Macro properties of the samples for different input micro parameters are presented and used to obtain the analytical CPT results. Comparison between the numerical simulations and analytical solutions show good agreement.